Centennial records of Polycyclic aromatic hydrocarbons and black carbon in Altay Mountains peatlands, Xinjiang, China - Luo, Nana; Wen, Bolong; Bao, Kunshan; Yu, Rui; Sun, Jing; Li, Xiujun; Liu, Xingtu (Frontiers in Ecology and Evolution, 2022)
Black carbon (BC) is an important inert carbon component in the cycling process of surface carbon. Polycyclic aromatic hydrocarbons (PAHs) are a kind of thick cyclic organic compounds with carcinogenic, teratogenic, and mutagenic effects. The incomplete burning process of biomass and carbolic fuel is the important source of their co-occurrence. This study collected a 60-cm peat core from the Jiadengyu (JDY), Altay Mountain. The core was dated using the 210Pb and 137Cs methods. The results showed BC, total organic carbon, and PAHs of the JDY peat core to be 1.14–72.6 mg g−1, 17.09–47.2%, and 260.58–1,610.77 ng·g−1, respectively. δ13CBC was between −31.5 and − 29.4‰ (mean of −30.56‰). The results of scanning electron microscopy (SEM) indicated irregular or lumpy peat BC particles, retaining a plant fiber structure. δ13CBC, ratios of PAHs, and the SEM revealed that the BC to be the dominant source of biomass combustion in the peatland. BC showed an increasing trend between 1950 and 1980, after which it decreased. The discrepancy between the change in BC and δ13CBC from the national pattern of BC emission likely reflects the effect of local agricultural exploration, and thus an increase in crop burning.